Evaluation of Financial Performance on The Stock Price of State-Owned Enterprises Listed on The Indonesia Stock Exchange 2015-2022 - Baharuddin , Gunawan (INQUISITIVE : International Journal of Economic, 2024)
The assessment of a company's financial performance involves ratio analysis, including profitability, leverage, and activity, which provides a deep understanding of the entity's financial performance and its impact on efficiency and investment feasibility, including its influence on stock prices. This research focuses on the assessment of financial performance on stock prices of state-owned construction companies (ADHI, WIKA, PTPP, WSKT) during the period 2015-2022. The purposive sampling method was used for sample selection with data in the form of published secondary data. Multiple linear regression analysis was conducted to evaluate the relationship between variables. The results show that profitability (ROE) does not have a significant effect on stock prices, while leverage (DER) and activity (TATO) have a significant effect on stock prices. With a determinant value (R2) of 92.3%, it means that these variables contribute significantly to the stock price, while the remaining 7.7% is explained by other factors not used in this study.